Development and Security in Southern Europe and the Mediterranean Area - Francesco Citarella (European Regional Science Association (ERSA), 2006)
Over the course of the years, the Mediterranean region has been analysed from many different perspectives and defined on the basis of the specific approach followed at the time (i.e. historic-cultural political, economical, functional etc.). On this occasion I would like to avoid ulterior interpretations and focus attention above all on the need for a course of development to guarantee security in Southern Europe. I don't want to suggest that Europe should take on the role of a top power, but rather, that Europe can aspire to leadership, in a certain sense, considering that capitalist globalisation has in the meantime become consolidated and that space for independent strategies that are not those of the management of well constituted interests, has been removed. It has been opportune and right to concentrate on the East of Europe over the last ten years, but on the twenty first century's agenda of security and development we should not underestimate the relevance of the Mediterranean. For the countries of the Mediterranean, therefore, there is no other alternative, and for the European countries the alternative remains that of the "wall"; a project not only immoral but also unfeasible because as history has demonstrated, divisions never support the drive of men. From these considerations which emerged during the course of my studies and research, the idea of elaborating a "MASTER PLAN FOR THE MEDITERRANEAN AREA", gradually took shape, in which the roles of the individual territories, the duties of the institutional subjects and the actions to undertake in a co-ordinated way, in the light of (a) a new international order and (b) the disparity and the different directions of the forces in the field.
Keywords: 330